Variability of Winter Snow Properties on Different Spatial Scales in the Weddell Sea. Issue 12 (6th December 2018) - Arndt, Stefanie; Paul, Stephan
Abstract: The snow cover on Antarctic sea ice persists during most of the year, contributing significantly to the sea ice mass budget due to comprehensive seasonal transition processes within the snowpack as well as at the snow/ice interface. Consequently, snow on sea ice varies not only in depth but also in particular in its physical characteristics such as snow density and stratigraphy. In order to quantify the heterogeneous nature of the Antarctic snowpack on different spatial scales, that is, small (<10 m), floe‐size (1‐2 km), and regional (seasonal/perennial ice) scales, we present here a case study of snow analyses in the Weddell Sea in austral winter 2013. The resulting high variability of snow parameters in the basal snow layer reveals the need to distinguish between seasonal and perennial ice regimes, when retrieving, for example, snow depth using satellite microwave radiometry. Considering the full vertical snow column, a more detailed distinction of the perennial sea ice regime into, for example, more ice classes is suggested in order to represent the high variability range. For the internal snowpack variability, however, we identify the grain size variability as the main driver, while snow density variations can be neglected. Moving from regional to floe‐size scales, a similar variability range of the studied snow properties is found, suggesting that a large number of snow samples on a few floes is more crucial than covering a large region with fewer floe‐scale measurements. The spatiotemporally heterogeneous variability in snow accumulation, redistribution, and metamorphism is, however, too large to upscale the given findings beyond regional scale. Plain Language Summary: Snow on sea ice alters the properties of the underlying ice cover as well as associated exchange processes at the interfaces between atmosphere, sea ice, and ocean due to its highly insulative and reflective properties. The snow cover on Antarctic sea ice generally persists throughout the year but undergoes substantial seasonal changes in its internal snowpack properties, as, for example, snow density, grain size, and grain shape. However, the spatial variability of these properties is poorly understood, yet this knowledge is crucial for sea ice mass budget calculations as well as the analysis of satellite remote sensing data. In this case study, we present a comprehensive snow data set covering different spatial scales. Thus, snow was sampled on seasonal and perennial sea ice floes across the Weddell Sea, while one floe was more frequently sampled, respectively. An additional 10‐m transect allows to conclude also on small‐scale variability. Revealed scale‐dependent snow property variability is discussed in the context of assumptions in energy and mass budget calculations as well as in recent retrievals of, for example, sea ice thickness, from satellite remote sensing observations in the ice‐covered Southern Ocean. Key Points: Distinction between seasonal and perennial snow regimes is mandatory In the Weddell Sea, the same magnitude of snow property variability on regional and floe size scale is found Snow grain sizes dominates the spatial variability of the Weddell Sea snowpack, while snow density variability can be neglected